2012
DOI: 10.1186/1940-0640-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Return to drug use and overdose after release from prison: a qualitative study of risk and protective factors

Abstract: Background Former inmates are at high risk for death from drug overdose, especially in the immediate post-release period. The purpose of the study is to understand the drug use experiences, perceptions of overdose risk, and experiences with overdose among former prisoners. Methods This qualitative study included former prison inmates (N = 29) who were recruited within two months after their release. Interviewers conducted in-person, semi-structured interviews which expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
196
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 253 publications
(217 citation statements)
references
References 30 publications
7
196
0
1
Order By: Relevance
“…It is widely known that drug use is happening in prisons and jails [10][11] and that patients are at high risk of overdose and other addiction-related harms upon release from prison or jail [12]. Patients also are exposed to high-salt diets and cannot even access a heart-healthy diet should they desire to do so; the high sodium and high fat content of food available in these settings exacerbate conditions such as hypertension, congestive heart failure, and end-stage liver disease [13,14].…”
Section: Is Incarceration Status Clinically Relevant?mentioning
confidence: 99%
“…It is widely known that drug use is happening in prisons and jails [10][11] and that patients are at high risk of overdose and other addiction-related harms upon release from prison or jail [12]. Patients also are exposed to high-salt diets and cannot even access a heart-healthy diet should they desire to do so; the high sodium and high fat content of food available in these settings exacerbate conditions such as hypertension, congestive heart failure, and end-stage liver disease [13,14].…”
Section: Is Incarceration Status Clinically Relevant?mentioning
confidence: 99%
“…Binswanger et al (2012) also found that "the environments to which participants returned immediately following prison made it difficult to avoid relapse due to ubiquitous triggers to use" (p. 5). Rhodes (2002) is emphatic that harm reduction related to drug use has tended to centre on individual risk behaviour that is "context-free" (p. 86) rather than a recognition of risk environments impacting on relapse and drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Binswanger et al (2012) found relapse to drug use after release from prison related to depression, anxiety and frustration. Rhodes (2009), drawing on the work of Farmer, Connors, and Simmons (1996), linked drug use with socio-economic stress and stressful life events, conceptualising it as a form of self-medication for "oppression illness" (Rhodes 2009, p. 196).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations